70th birthday of Reinhard Folk (Condensed Matter Physics, 2015)
On April 29, 2015 Reinhard Folk - member of the Editorial Board of "Condensed Matter Physics", renowned expert in the fields of condensed matter physics, phase transitions and critical phenomena - celebrated his 70th birthday.